The Influence Of Accountability And Transparency In Realizing Good Public Services (At The Luwu District PDAM Office) - Irawan, Della Sinta; Idris, Hariany; Tikollah, M. Ridwan (Phinisi Applied Accounting Journal, 2023)
ABSTRACTThis research aims to determine the influence of accountability and transparency in realizing good public services. The object of the research is the Regional Drinking Water Company, which is one of the regional business units that operates in the distribution of clean water to the public or known as (PDAM). The instrument in this research is a questionnaire where PDAM staff are the respondents in this research. The variables in this research are accountability and transparency as independent variables. As for the public service variable, it is a dependent variable. The results of this research show that accountability and transparency have a positive influence in realizing good public services at the Luwu Regency PDAM office.  Penelitian ini bertujuan untuk mengetahui pengaruh akuntabilitas dan transparansi dalam mewujudkan pelayanan publik yang baik.Objek penelitian adalah Perusahaan Daerah Air Minum merupakan salah satu unit usaha Daerah yang bergerak pada pendistribusian air bersih bagi publik atau dikenal dengan (PDAM). Instrument pada penelitian ini adalah kuisoner dimana staf PDAM merupakan responden dalam penelitian ini. Variabel dalam penelitian ini adalah akuntabilitas dan transparansi sebagai variabel independent. Adapun untuk variabel pelayanan publik merupakan variabel dependent. Hasil dari penelitian ini menunjukkan bahwa akuntabilitas dan transparansi berpengaruh positif dalam mewujudkan pelayanan publik yang baik pada kantor PDAM Kabupaten Luwu.